PENINGKATAN PEMAHAMAN SISWA MA NU MRANGGEN MENGENAI TANGGUNGJAWAB PENGANGKUT DALAM PENGANGKUTAN NIAGA - Saiful Abib, Agus; Pujiastuti, Endah; Mulyani, Tri (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Public transportation is one of the transportation media that is very necessary for the community and the government to minimize the use of private transportation as well as congestion that is becoming more and more common in big cities in Indonesia. The use of public transportation is carried out by the government through State-Owned Enterprises (BUMN) and Privately-Owned Enterprises (BUMS) through land, sea and air transportation. Public transportation in the past 1 (one) decade has become the main center of attention for the central and regional governments in order to minimize the accident rate on public transportation and make various policies to protect passengers and their heirs if unwanted things happen. So far, many students do not know the responsibilities of carriers in public transportation, therefore it is necessary to do community service in the form of outreach to increase the understanding of MA NU Mranggen students regarding the responsibilities of carriers in public transportation. This service is carried out by means of lectures and direct questions and answers and evaluation by distributing questionnaires before and after the activity is carried out. This service is carried out by an implementation team consisting of 1 (one) chairperson, and 2 (two) members. The implementation team is lecturers at the Faculty of Law, University of Semarang who are competent in mastering material regarding the responsibilities of carriers in commercial transport. The results of the dedication which took the theme of the rights of persons with disabilities, based on an average increase of 70.0%.